The Excellence Baldrige Criteria in The Effectiveness of Higher Education Institutions Management - Paulo Henrique Barroso Menezes; Henrique Cordeiro Martins; Ronielton Rezende Oliveira (BBR: Brazilian Business Review, 2018)
This paper aims to analyze the antecedents of effectiveness of education management in seven units of a Higher Education Institution (IES, in Portuguese) located in the metropolitan region of Belo Horizonte, MG, Brazil. The research is a quantitative study and was applied in the case study format in the largest private Brazilian education organization listed in the stock market. Data sample were collected through a survey and the informants are directors, course coordinators, teachers and administrative staff. The results were obtained through the structural equation modeling in relation to Excellence Baldrige Criteria, and indicate the model proposed by this research, that the Strategic Planning and Operation Focus influence directly on the Effectiveness of Management. We verified the existence of a positive correlation between all the constructs of the Baldrige Excellence Model with the Effectiveness of Management of the HEI.